2005
DOI: 10.1111/j.1745-7254.2005.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium ferulate prevents amyloid-beta-induced neurotoxicity through suppression of p38 MAPK and upregulation of ERK-1/2 and Akt/protein kinase B in rat hippocampus1

Abstract: Aim: To observe whether an amyloid β (Aβ)-induced increase in interleukin (IL)-1β was accompanied by an increase in the p38 mitogen-activated protein kinase (MAPK) pathway and a decrease in the cell survival pathway, and whether sodium ferulate (SF) treatment was effective in preventing these Aβ-induced changes. Methods: Rats were injected intracerebroventricularly with Aβ [25][26][27][28][29][30][31][32][33][34][35] . Seven days after injection, immunohistochemical techniques for glial fibrillary acidic prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Activated p38MAPK is observed in human AD brain tissue [57] and in AD-relevant animal models [58,59] , and cell culture studies strongly implicate p38MAPK in the increased production of proinflammatory cytokines in the glia activated by Aβ [60] . The activation of p38MAPK in neuronal cells has been associated with IL-1 and hyperphosphorylated tau in AD [61] .…”
Section: Discussionmentioning
confidence: 99%
“…Activated p38MAPK is observed in human AD brain tissue [57] and in AD-relevant animal models [58,59] , and cell culture studies strongly implicate p38MAPK in the increased production of proinflammatory cytokines in the glia activated by Aβ [60] . The activation of p38MAPK in neuronal cells has been associated with IL-1 and hyperphosphorylated tau in AD [61] .…”
Section: Discussionmentioning
confidence: 99%
“…Sodium ferulate restored the arrangement and the number of hippocampal CA1 pyramidal neurons in the hippocampus of young adult rats subjected to b-amyloid-(1-40) (67) as well as the arrangement of hippocampal CA1 pyramidal neurons in the hippocampus of aged rats (68). This ferulic acid salt has also been shown to significantly inhibit b-amyloid-induced astrocyte activation and inflammation and suppress the increase in caspase-3 activity and expression of caspase-3 protein in the rat hippocampus (66,68). It has been demonstrated (69) that sinapic acid and its derivatives tenuifoliside B and 3,6′-disinapoylsucrose inhibited KCN-induced hypoxia and scopolamine-and CO 2 -induced memory impairment in mice.…”
Section: Phenolic Acids As Efficient Ache and Bche Inhibitorsmentioning
confidence: 99%
“…Sodium ferulate partly reduced the decrease in phosphorylated extracellular signal-regulated kinases ERK1 and ERK2 and completely reversed the decrease in phosphorylated Akt/protein kinase B induced by b-amyloid- (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in the hippocampal regions of the rat brain (66). Also, sodium ferulate inhibited a b-amyloid-(1-40)-induced increase in phosphorylated-p38 mitogen-activated protein kinase (MKK3/MKK6), partly prevented a decrease in phosphorylated MAPKAPK2 and Hsp27 expression, and inhibited the activation of caspase cascades (caspase-3, caspase-7 and caspase-3 activities) (67).…”
Section: Phenolic Acids As Efficient Ache and Bche Inhibitorsmentioning
confidence: 99%
“…33,34) It has been confirmed that Aβ [25][26][27][28][29][30][31][32][33][34][35] can cause neural cell death, induced suppression of extracellular signal-regulated kinase (ERK) or its downstream intermediate CREB in neuroblastoma cells and in rats after injection of Aβ [25][26][27][28][29][30][31][32][33][34][35] . 35,36) In the present study, we thus used Aβ [25][26][27][28][29][30][31][32][33][34][35] to induce cytotoxicity in neurons and SH-SY5Y cells. It was found that Aβ [25][26][27][28][29][30][31][32][33][34][35] insult markedly decreased cell viability and synapsin-1 protein level …”
Section: Discussionmentioning
confidence: 99%